Employment benefits and job retention: evidence among patients with colorectal cancer - Christine M. Veenstra; Paul Abrahamse; Todd H. Wagner; Sarah T. Hawley; Mousumi Banerjee; Arden M. Morris (Cancer Medicine, 2018)
Abstract A “health shock,” that is, a large, unanticipated adverse health event, can have long‐term financial implications for patients and their families. Colorectal cancer is the third most commonly diagnosed cancer among men and women and is an example of a specific health shock. We examined whether specific benefits (employer‐based health insurance, paid sick leave, extended sick leave, unpaid time off, disability benefits) are associated with job retention after diagnosis and treatment of colorectal cancer. In 2011–14, we surveyed patients with Stage III colorectal cancer from two representative SEER registries. The final sample was 1301 patients (68% survey response rate). For this study, we excluded 735 respondents who were not employed and 20 with unknown employment status. The final analytic sample included 546 respondents. Job retention in the year following diagnosis was assessed, and multivariable logistic regression was used to evaluate associations between job retention and access to specific employment benefits. Employer‐based health insurance (OR = 2.97; 95% CI = 1.56–6.01; P = 0.003) and paid sick leave (OR = 2.93; 95% CI = 1.23–6.98; P = 0.015) were significantly associated with job retention, after adjusting for sociodemographic, clinical, geographic, and job characteristics.